JALBTCX Coastal Mapping for the USACE - Wozencraft, Jennifer M.; Lillycrop, W. Jeff (The International Hydrographic Review, 2006)
The Joint Airborne Lidar Bathymetry Technical Center of Expertise (JALBTCX) provides spatial data to support the U.S. Army Corps of Engineers (USACE) National Coastal Mapping Program (NCMP) and hurricane damage evaluation and response. The NCMP was designed to provide topographic and bathymetric elevation data with accompanying digital, geo-referenced imagery to USACE District engineers and scientists. The data support monitoring and maintenance of federal navigation and shore protection projects, and regional sediment management. The main source of these data is the CHARTS system, which is owned by the U.S. Naval Oceanographic Office and operated through the JALBTCX. The NCMP leverages other federal entities’ funding, equipment, and mapping programs to efficiently provide these data to the USACE, and avoid duplication of coastal mapping initiatives.